al-Tafriq al-qada'iy bayna al-zawjayn fi al-qanun al-'Iraqiy : dirasat tahliliyah fiqhiyah = Judicial dissolution of marriage in Iraqi law : an analytical study in Islamic jurisprudence / Majid Idris Jumaah - Jumaah, Majid Idris (2014)
This study comprises a study of the causes of judicial separation between the spouses in Iraqi law and its analysis as an Islamic perspective. It is an analytical study that goes over the legal clauses relating to judicial separation in the Iraqi Law, with a field study on one governorate in region of Kurdistan in Iraq. The researcher has conducted the research in the offices of the Social Researcher and in the Statistics Division in the Appeals Court in Duhok governorate in Iraq, on the judicial separation of spouses’ data from the year 8002 until the end of year 8008, citing examples of the conclusive decisions to separate the spouses. This thesis aims at showing the court’s authority in separating the married couple, the extent of such authority, and the legal clauses relating to the judicial separation between spouses in Iraqi Law, and aims also at studying and analyzing such clauses within the framework of the Islamic Law. The thesis aims as well at presenting the reasons for spouses’ separation judgment, that either they common to both spouses, such as dissention between the spouses or ill companionship, or they can be from the husband, and showing their rulings in the Iraqi law, analyzing them within the framework of the Islamic Shari’ah Law, and citing the most common reasons for separation verdicts in Dohuk province. The study for this research is conducted three methodologies as follows. First is the data collection methodology. This methodology is used to do the scientific data collection from the literature in the library, where the researcher collected the scientific data on the Iraqi law and Islamic Shari’ah Law. Second is the Data Analysis Methodology. Legal clauses relating to the judicial separation between spouses were studied and analyzed from the Islamic perspective. Third is the Field Research Methodology. Field research is to carry out by going over the judicial separation of spouses verdicts’ data and going over samples of the conclusive separation decisions at the Personal Status Court in Duhok province. The research reached a number of conclusions. The most important results are the following. The Iraqi legislator needs to revise some of the legal clauses relating to spouses separation judgments, especially the kind of separation, and to follow the amendments passed by the Kurdistan province government in Iraq. The Iraqi legislator needs also to pay more attention to the issue of the Social Researcher. Among the most important reasons for the differences among Islamic Fiqh scholars over judicial separation is that there is no definitive explicit text in Quran nor in Sunnah indicating separation permissiveness or prevention. Another reason is that all rulings in the separation cases were rulings issued by the companions, where such rulings’ authentications or interpretations can be controversial. Another reason is that all the Fiqh scholars who ruled with separation cited the reason for such ruling as being the harm, where if the harm was confirmed the ruling was the separation, but if the harm was not confirmed then no separation would be ruled. That was relying on the fundamental principle that says that the ruling follows its reason whether existing or absent. And the reason for separation ruling is the harm.